How to check whether a blood pressure monitor has been properly validated for accuracy. Issue 12 (5th October 2020) - Picone, Dean S.; Padwal, Raj; Campbell, Norm R. C.; Boutouyrie, Pierre; Brady, Tammy M.; Olsen, Michael Hecht; Delles, Christian; Lombardi, Cintia; Mahmud, Azra; Meng, Yaxing; Mokwatsi, Gontse G.; Ordunez, Pedro; et al.
Abstract: Hypertension guidelines recommend that blood pressure (BP) should be measured using a monitor that has passed validation testing for accuracy. BP monitors that have not undergone rigorous validation testing can still be cleared by regulatory authorities for marketing and sale. This is the situation for most BP monitors worldwide. Thus, consumers (patients, health professionals, procurement officers, and general public) may unwittingly purchase BP monitors that are non‐validated and more likely to be inaccurate. Without prior knowledge of these issues, it is extremely difficult for consumers to distinguish validated from non‐validated BP monitors. For the above reasons, the aim of this paper is to provide consumers guidance on how to check whether a BP monitor has been properly validated for accuracy. The process involves making an online search of listings of BP monitors that have been assessed for validation status. Only those monitors that have been properly validated are recommended for BP measurement. There are numerous different online listings of BP monitors, several are country‐specific and two are general (international) listings. Because monitors can be marketed using alternative model names in different countries, if a monitor is not found on one listing, it may be worthwhile cross‐checking with a different listing. This information is widely relevant to anyone seeking to purchase a home, clinic, or ambulatory BP monitor, including individual consumers for use personally or policy makers and those procuring monitors for use in healthcare systems, and retailers looking to stock only validated BP monitors.